Innovation in Materials Science and Engineering Proceedings of ICEMIT 2017, Volume 2 - Chattopadhyay, Jayeeta; Singh, Rahul; Prakash, Om.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book features the scientific work on materials science presented at the International Conference on Energy, Materials and Information Technology, 2017 at Amity University Jharkhand, India. It highlights all aspects of materials, from synthesis to innovative applications, and from physical characterizations to cost-effectiveness. It also covers essential and state-of-the-art research work on various engineering materials with important physical characteristics. This multidisciplinary book is aimed at scientists, academics, research scholars and students from all areas who are interested in understanding the current research in the field of materials science. .
Chapter1.Effect of Polymer Modification on Structural and Mechanical Properties of Concrete using Epoxy Emulsion as the Modifier -- Chapter 2. Moisture Absorption Behavior and Mechanical Properties of Banana Fiber Reinforced Fly Ash /Epoxy Composites -- Chapter 3. Effect of chemical modification on physical properties of natural fiber reinforced hybrid polymer composites.
Keywords: Materials; Nanotechnology; Catalysis; Force and energy; Materials Engineering; Nanotechnology; Materials for Energy and Catalysis